The Contribution of Student Management, Guidance and Counseling Services, and Parental Roles to the Character Values of Junior High School Students - Dwitariani, Ni Kadek Nonik (Universitas Pendidikan Ganesha, 2025)
The lack of effective collaboration among schools, families, and educational support services poses a significant challenge in shaping students' character. Character values, which should serve as the foundation of students' personalities, often fail to develop optimally due to weak synergy among these elements. This study aims to analyze the contributions of student management, guidance and counseling services, and parental involvement to the enhancement of students’ character values. Employing a quantitative approach with an ex post facto design, the study involved 587 students as the research population. Data were collected using a Likert-scale questionnaire, which had been tested for content and item validity, supported by documentation. Data analysis techniques included simple regression, multiple regression, and partial correlation. The findings indicate that all three variables—student management, guidance and counseling services, and parental involvement—significantly contribute to the development of student character. Among them, guidance and counseling services were found to have the most dominant influence. The study concludes that integrating the roles of schools, counselors, and parents is essential in creating an educational ecosystem that fosters character building. The practical implication suggests that enhancing the quality of counseling services and school–parent communication can be an effective strategy for strengthening student character development in a sustainable manner.